Tectonic DSAEK for the Management of Impending Corneal Perforation. (5th December 2012) - Graue-Hernandez, Enrique O.; Zuñiga-Gonzalez, Isaac; Hernandez-Camarena, Julio C.; Jaimes, Martha; Chirinos-Saldaña, Patricia; Navas, Alejandro; Ramirez-Miranda, Arturo
Abstract : Purpose . To report a case of severe corneal thinning secondary to dry eye treated with a tectonic Descemet stripping automated lamellar keratoplasty (DSAEK) and amniotic membrane graft. Methods . A 72-year-old man with a history of long standing diabetes mellitus type 2 and dry eye presented with 80% corneal thinning and edema on the right eye and no signs of infectious disease, initially managed with topical unpreserved lubrication and 20% autologous serum drops. Eight weeks after, the defect advanced in size and depth until Descemetocele was formed. Thereafter, he underwent DSAEK for tectonic purposes. One month after the procedure, the posterior lamellar graft was well adhered but a 4 mm epithelial defect was still present. A multilayered amniotic membrane graft was then performed. Results . Ocular surface healed quickly and reepithelization occurred over a 2-week period. Eight months after, the ocular surface remained stable and structurally adequate. Conclusion . Tectonic DSAEK in conjunction with multilayered amniotic graft may not only provide structural support and avoid corneal perforation, but may also promote reepithelization and ocular surface healing and decrease concomitant inflammation.